Use of Sodium Bicarbonate in Diabetic Hyperglycemic Emergencies - Diana Machado Ramírez; Manuel Licea Puig (Universidad de las Ciencias Médicas de Cienfuegos, 2013)
Background: diabetic ketoacidosis and hyperosmolar hyperglycemic nonketotic state are two of the major metabolic emergencies that may occur. These conditions are not always treated properly. Objective: to describe the metabolic hyperglycemic emergencies in diabetic patients treated in the Intensive Care Unit, and to assess the use of sodium bicarbonate. Methods: a descriptive, cross-sectional study was conducted including 52 patients admitted to the Intensive Care Unit of the Enrique Cabrera Hospital from 2000 through 2007. The following variables were analyzed: type of diabetes mellitus, type of acute complication, use or not of sodium bicarbonate, blood gases, ionogram and progress of patients. Kitabchi criteria were used for the diagnosis of diabetic ketoacidosis and its severity and for the diagnosis of the hyperglycemic state as well. Criteria proposed by an Expert Committee of the American Diabetes Association and a World Health Organization Expert Committee were adopted for the diagnosis of diabetes and its classification. Results: diabetic ketoacidosis was confirmed in 57,5 % of type 1 diabetic patients and in 42,5 % of those with type 2 diabetes. Hyperosmolar hyperglycemic nonketotic state was observed in 23,0 % of type 2 diabetics. There was not any death among patients with diabetic ketoacidosis who did not use sodium bicarbonate whereas 80,0 % of patients with hyperglycemic state who used it died. Conclusions: diabetic ketoacidosis was the most common complication. Mortality due to ketoacidosis and hyperosmolar hyperglycemic nonketotic state was high. Sodium bicarbonate was not properly used.